Political events in Ukraine in Western mass media (2014-2022) - Inoyatov Hajiakbar (My University, 2023)
The tasks of the diploma work on the topic "Political events in Ukraine in the Western media (2014-2022)" can be as follows: − Examine divergent perspectives and agendas in the coverage of Ukrainian events by Russian and Western media, focusing on linguistic choices. − Identify key conclusions and discussions regarding political events in Ukraine based on media coverage analysis. − Utilize linguistic analysis tools (stylistic devices, syntactic structures) to examine language use in media representations. − Identify and analyze key themes and narratives in the representations of political events in Ukrainian media. The object of this thesis paper is to analyze the linguistic aspects of Western mass media coverage of political events in Ukraine between 2014 and 2022. The subject of this thesis paper is the political events in Ukraine between 2014 and 2022 as portrayed in Western mass media. It focuses on the language used, framing techniques, and narrative construction employed by journalists and media outlets in their coverage of the Ukrainian conflict.
Keywords: Linguistics; Political Events; Ukraine; Western Mass Media